Disembodied Icons: Analysing Headless Female Representations in Hollywood Thriller Posters - Khan, Mahaam; Akhtar, Rizwan (Journal of Ecohumanism, 2024)
This study examines the prevalence of disembodied representations of women in Hollywood thriller posters, focusing on headless or partially obscured female figures. Using Charles Sanders Peirce’s semiotic theory and Erving Goffman’s frame analysis, the research analyses the visual encoding of power, objectification, and gender in ten iconic film posters, including Suicide Squad, Buffy the Vampire Slayer, Wonder Woman, and The Wolf of Wall Street. The analysis reveals how the partial or complete erasure of women’s faces in these posters functions as a strategic tool to both eroticize and objectify female characters. Semiotic elements, such as body positioning, attire, and accessories (e.g., weapons, and money), signify the duality of women as both powerful agents and passive objects of desire. Through Goffman’s framework, the study underscores how these disembodied representations perpetuate stereotypes of femininity, subordination, and sexualization, while also reinforcing a hierarchical gendered power dynamic. Ultimately, the findings illuminate how Hollywood thriller posters exploit the disembodiment of female characters to negotiate their place within the broader cultural discourse on gender, agency, and visual spectacle.